What comes first? Publishing business or publishing studies? (Libellarium: journal for research in the field of information and related sciences, 2015)
The aim of this paper is to analyze and compare publishing studies, their programmes at the undergraduate and graduate levels and scholars involved in the teaching of publishing courses at the top universities around the world and in Croatia. Since traditional publishing business is rapidly changing, new skills and new jobs are involved in it. The main research question is: Can modern publishing studies produce a modern publisher? Or, is it the other way around? The hypothesis of the paper is that scholars involved in the teaching of publishing courses at the top universities around the world have a background in publishing business. So, can they prepare their students for the future and can their students gain competencies they need to compete in a confusing world of digital authors and electronic books? The research methods used were content analysis and comparison. Research sample included 36 university publishing programmes at the undergraduate and graduate level worldwide (24 MA, 12 BA). The research sample was limited mainly to the English-speaking countries. In most non-English-speaking countries, it was difficult to analyse the programme curriculum in the native language because the programme and course description did not exit. In the data gathering phase, a customized web application was used for content analysis. The application has three main sections: a list of websites to evaluate, a visual representation of the uploaded website and a list of characteristics grouped by categories for quantifying data. About twenty years ago, publishing was not considered a separate scientific branch in Croatia. Publishing studies are therefore a new phenomenon to both scholars and publishers in Croatia. To create a new, ideal publishing course, can we simply copy global trends or is it better to create something of our own?
Keywords: publishing studies; publishing course; publishing business